Using of virtualized IT-infrastructure under normal operation of automation systems of technological objects - Вавулін, Петро Андрійович; Бойко, Тетяна Владиславівна (Technology audit and production reserves, 2017)
Taking into account the global trends and experience of implementation of modern information technologies in production processes, with the aim of updating and increasing the competitiveness of Ukrainian industrial complexes, the issues and methods for using of hardware and software and technological solutions in the field of virtualization are considered. The main method of research is computer simulation – simulation of real automation systems (including server component) using the tools of virtualization (Microsoft Hyper V). The essence of the method is creation of a virtual environment (infrastructure), including primary and backup server with process control system and workstations. Virtual machines of automation systems are fully meet their physical analogues by heir characteristics. The ways of using of traditional automation systems, which are deployed on the basis of virtualization platform Hyper V, are considered. The main way of using of traditional software automation is their deployment on the basis of server operating system with support for one of the many virtualization technologies, such as: MS Hyper V, VMWare VSphere, Citrix Xen Server, and others. An opportunity of practical operation of automation systems on the basis of virtualized hardware and software server complex with the thin clients as workstations is proved for Experion PKS system and Honeywell C200 controller. The process control system is deployed in a virtualized environment on the basis of server (Windows Server 2012 R2) and normal (Windows 10) operating systems. The possible positive effect of implementation of modern IT infrastructure for technological objects is also analyzed. It lays in the fact of theoretically increase of fault tolerance level, practical simplification of system administration, and creation of bank for backup of virtual machines. This result is associated with a more rational and efficient use of capabilities of modern computer systems (CPU and RAM), data storage systems (using of RAID hard drives) and software.